2009
DOI: 10.5694/j.1326-5377.2009.tb02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Child homicide in New South Wales from 1991 to 2005

Abstract: Objective: To examine the circumstances of homicides of children in New South Wales from 1991 to 2005. Design and setting: Retrospective analysis of all identified child homicides in NSW from 1991 to 2005, based on data on offenders and victims obtained from crime statistics, documents located by systematic searches of legal databases and media reports, and medicolegal reports of offenders who committed child homicides during psychotic illness. Main outcome measures: Demographic characteristics of homicides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 9 publications
(13 reference statements)
2
17
0
1
Order By: Relevance
“…For example, Nielssen, Large, Westmore, and Lackersteen (2009) found in their Australian study that 7 of 157 (4%) child homicide offenders committed filicide-suicide. This is a considerably lower figure than the 33% reported in this study.…”
Section: The Proportion Of Filicide-suicides Remains Relatively Highmentioning
confidence: 99%
“…For example, Nielssen, Large, Westmore, and Lackersteen (2009) found in their Australian study that 7 of 157 (4%) child homicide offenders committed filicide-suicide. This is a considerably lower figure than the 33% reported in this study.…”
Section: The Proportion Of Filicide-suicides Remains Relatively Highmentioning
confidence: 99%
“…As there are few studies specific to the factors associated with NAHI (Jayawant et al ., ; Kelly et al ., ; Ricci et al ., ; Ryan et al ., ), comparisons must also be made with general child abuse research. This shows that families in which abuse occurs are characterised by high rates of substance abuse, unemployment, forensic histories, mental illness and financial hardship (Cavanagh et al ., ; Delfabbro et al ., ; Dolan et al ., ; Nielssen et al ., ; Wilczynski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have suggested that the magnitude of fatal child abuse has been underestimated (Herman-Giddens et al, 1999;Crume et al, 2002). Young child and infant homicide are frequently related to child abuse and psychiatric dysfunction in a parent or custodial adult (Friedman et al, 2005;Jenny & Isaac, 2006;Nielssen et al, 2009). The problem of young child and infant homicide in the United States began receiving increased attention in the 1960's (Adelson, 1961;Kempe et al, 1962).…”
Section: Introductionmentioning
confidence: 99%